2014
DOI: 10.1186/alzrt273
|View full text |Cite
|
Sign up to set email alerts
|

Differentially charged isoforms of apolipoprotein E from human blood are potential biomarkers of Alzheimer’s disease

Abstract: IntroductionAlzheimer’s disease (AD) is the major cause of dementia among the elderly. Finding blood-based biomarkers for disease diagnosis and prognosis is urgently needed.MethodsWe studied protein distributions in brain tissues, cerebrospinal fluid (CSF), and blood of AD patients by using proteomics and a new proteomic method that we call “2D multiplexed Western blot” (2D mxWd). This method allows us to determine in multiple samples the electrophoretic patterns of protein isoforms with different isoelectric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…In a mouse model of brain amyloid, APOE3 was preferentially extracted in TBSX compared to APOE4 (Youmans et al, 2012), supporting a connection between this characteristic of APOE and AD pathological changes. In the human hippocampus, APOE in APOE -ε4 carriers has a lower pI (indicative of increased sialylation) compared to APOE -ε3 carriers (Alzate et al, 2014). APOE -ε3 carriers with AD also had more of this lower pI APOE compared to APOE -ε3 carriers without AD (Alzate et al, 2014), suggesting that APOE modification may represent not only an APOE -ε4-associated biomarker, but also an AD associated biomarker.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a mouse model of brain amyloid, APOE3 was preferentially extracted in TBSX compared to APOE4 (Youmans et al, 2012), supporting a connection between this characteristic of APOE and AD pathological changes. In the human hippocampus, APOE in APOE -ε4 carriers has a lower pI (indicative of increased sialylation) compared to APOE -ε3 carriers (Alzate et al, 2014). APOE -ε3 carriers with AD also had more of this lower pI APOE compared to APOE -ε3 carriers without AD (Alzate et al, 2014), suggesting that APOE modification may represent not only an APOE -ε4-associated biomarker, but also an AD associated biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…In the human hippocampus, APOE in APOE -ε4 carriers has a lower pI (indicative of increased sialylation) compared to APOE -ε3 carriers (Alzate et al, 2014). APOE -ε3 carriers with AD also had more of this lower pI APOE compared to APOE -ε3 carriers without AD (Alzate et al, 2014), suggesting that APOE modification may represent not only an APOE -ε4-associated biomarker, but also an AD associated biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…The dominant morphologies among hits for both proteins were either individual rods or needles or clusters of rods or needle-like objects (Figure 3) and the majority of hits were detected after relatively long incubation periods, typically at the three-week timepoint. Some trends were identified in the hits obtained, particularly the prevalence of mono or divalent inorganic salts, mid-range or very low molecular weight PEGs, and pH conditions at or above the isoelectric point of the apolipoprotein (5.56 and 5.65 for ApoA1 and ApoE4 respectively [67]) (Figure S4). other polymer precipitants of varying molecular weight, salts, and a variety of pHs and buffer conditions, as well as commercially available screens from Hampton Research (including PEGRx HT, PEG Ion HT, Crystal Screen HT, Index, Salt Rx HT, Silver Bullet with PEG3350 pH 6.8 precipitants, Grid Screen Ammonium Sulfate, Slice pH, Ionic Liquids, and Polymer Screen) and molecular dimensions (MemGold screen) used as received or lightly modified [65,66].…”
Section: Crystallization Optimizationmentioning
confidence: 99%
“…There are three major alleles of ApoE, namely ApoE2, ApoE3, and ApoE4, and there is a subtype specificity in the development and prognosis of disease. 21,22 Several studies have shown that ApoE4 carriers are more likely to develop AD, while ApoE2 may reduce the risk of AD. In addition, ApoE4 carriers have a worse prognosis for craniocerebral trauma compared with ApoE2 or ApoE3 carriers.…”
Section: Figurementioning
confidence: 99%